Evaluation of the 3 mm Thickness Splint Therapy on Temporomandibular Joint Disorders (TMDs) - Nihat Akbulut; Ahmet Altan; Sibel Akbulut; Cemal Atakan (Pain Research and Management)
Objective. This study aimed at finding out whether the 3 mm thickness of stabilization splints has positive or negative effects on all temporomandibular disorder (TMD) symptoms. Materials and Methods. The statistical calculation included 25 (22 females; 3 males) TMD patients who received 3 mm thickness stabilization splint therapy. They were evaluated according to follow-up treatment period, TMD pain, muscle pain, mouth opening, diet score, and splint usage time per day. Results. There was important treatment success that 22 (88%) of patients were totally healed. There was not any remarkable effect or advancement of splints on total healings of TMDs in first 3 months’ period (11/25 patients, 44%). The mouth opening mean reached 38, 67 mm at 6 months and 41 mm at 12 months with remarkable success. Except one (4%) patient, other 24 (96%) patients had a normal diet score of 3 at the end of splint therapy. There was no correlation between splint usage duration a day and total healing of TMDs. Conclusion. We conclude that 3 mm splint therapy should maintain at least 6 months to achieve remarkable results. Splint should be used at least 12 h a day consistent with our results. Finally, diet score should be incorporated with TMD pain and amount of mouth opening; hence, we advise to use in one term as “total healing.”